1999
DOI: 10.1177/002076409904500106
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward the Mentally Ill in a Sample of Professionals Working in a Psychiatric Hospital in Beijing (China)

Abstract: The attitudes of psychiatric doctors and nurses toward the mentally ill in a large urban psychiatric hospital in China were compared using the Community Attitudes toward the Mentally Ill (CAMI). Data indicated that the attitude of professionals differed on 11 of the 40 questions of this instrument. Those questions are divided along 4 dimensions: authoritarianism, benevolence, social restrictiveness and rehabilitation in the community. Results showed that psychiatric doctors have a more liberal and positive att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 27 publications
1
55
0
3
Order By: Relevance
“…These findings are in contrast to research which showed that personal experience with TBI did not influence the misconceptions held by nursing students 24 . However, greater experience has been shown to influence the attitudes individuals hold towards people with mental health problems in both positive, 37,38 and negative, 39 directions.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in contrast to research which showed that personal experience with TBI did not influence the misconceptions held by nursing students 24 . However, greater experience has been shown to influence the attitudes individuals hold towards people with mental health problems in both positive, 37,38 and negative, 39 directions.…”
Section: Discussionmentioning
confidence: 99%
“…Outros estudos, ao contrário, demonstraram que os profissionais de saúde mental apresentaram atitudes mais positivas para com os doentes mentais -o contato direto foi um importante fator para isso -do que a população geral 5,[9][10][11] . No Brasil, há poucos estudos que avaliam as atitudes de profissionais de saúde mental com relação aos indivíduos com transtornos mentais.…”
Section: ▄ Introduçãounclassified
“…Yet, it was only in recent times that interest began to be shown in the attitudes toward and knowledge about mental illness (Cormack & Furnham, 1998), and a majority of the studies published on this subject were from western societies. Of these, the majority focused on the attitude of the public, while only a few others explored specific groups such as the health professionals (Sevigny et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…While there are some commonalities regarding the attitude toward mental illness that cut across cultural boundaries (Adler & Wahl, 1998;Herzig & Thole, 1998;Sevigny et al, 1999;Jorm et al 1999;Crisp et al, 2000;Wilson et al, 2000), certain unique attitudes have been described in some cultures (Kucharska-Pietura et al, 1998;Morrison & Thornton, 1999;Arikan et al, 1999;Madianos et al, 1999;Kurihara et al, 2000). This cultural diversity in the knowledge about and attitude toward mental illness has therefore made it necessary to explore this subject in a wide range of cultures, especially developing ones in the South Pacific region.…”
Section: Introductionmentioning
confidence: 99%